Deep ice core drilling to 2503 m depth at Dome Fuji, Antarctica - Fujii, Yoshiyuki; Azuma, Nobuhiko; Tanaka, Yoichi; Nakayama, Yoshiki; Kameda, Takao; Shinbori, Kunio; Katagiri, Kazuo; Fujita, Shuji; Takahashi, Akiyoshi; Kawada, Kunio; Motoyama, Hideaki; Narita, Hideki; et al. (2002)
P(論文) Deep ice core drilling was carried out at Dome Fuji, Antarctica in 1995 and 1996 from the bottom of the casing installed in 1993 and reached 2503.52m in December 1996. We used a JARE type electromechanical drill with a core barrel of 2.2m length. Total numbers of ice corings and chip collections were 1369 and 837 respectively. The mean coring depths per run and per day were 1.75m and 8.21m, respectively. Quality of ice cores was perfect throughout the whole depth, even in the brittle zone. We report the outline of the system, coring performance, and troubles encountered. departmental bulletin paper